1997
DOI: 10.1177/026565909701300104
|View full text |Cite
|
Sign up to set email alerts
|

'Teacher talk' with children with language disorders: four case studies II

Abstract: In this second part of a study which examined the general characteristics of the talk of language unit teachers and the effect it had on that of their pupils, the similarities and differences found amongst the teachers are discussed and illustrated by examples of teacher-child interaction. The possible implications for teacher practice are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Drew (1981), examining a large body of mainstream classroom data, reports that teachers use a mixture of other-initiated other-repair and otherinitiated self-repair, but comments little on the frequency or function of these repair strategies. Sadler and Mogford-Bevan (1997) nd that up to half of language unit teachers' repair moves are other-initiated other-repair, the form less likely to be found in adult interaction. They helpfully distinguish between repair turns designed as reformulations and those constituting clari cation requests.…”
Section: Fragment R2mentioning
confidence: 94%
See 4 more Smart Citations
“…Drew (1981), examining a large body of mainstream classroom data, reports that teachers use a mixture of other-initiated other-repair and otherinitiated self-repair, but comments little on the frequency or function of these repair strategies. Sadler and Mogford-Bevan (1997) nd that up to half of language unit teachers' repair moves are other-initiated other-repair, the form less likely to be found in adult interaction. They helpfully distinguish between repair turns designed as reformulations and those constituting clari cation requests.…”
Section: Fragment R2mentioning
confidence: 94%
“…Neutral requests such as 'pardon' provide no support, whereas speci c or direct requests can function as a supportive device when they help to indicate the precise nature of the problem to the child. Sadler and Mogford-Bevan (1997) found that this type of support was occasionally used by language unit teachers (see fragment R2 above).…”
Section: Fragment R2mentioning
confidence: 99%
See 3 more Smart Citations